Utilization of Wetland Vegetation as Ethnobotany by the Community of Burai Village: Identification Study and Local Wisdom - Hastiana*, Yetty; Anjelia, Bella; Sumah, Astrid Sri Wahyuni; Putra, Dani Jaya (Jurnal Pendidikan Sains Indonesia, 2025)
The utilization of wetland vegetation as ethnobotany by the people of Burai Village reflects the strong relationship between local communities and their surrounding environment. This research aims to identify wetland plants used by the community and document their ethnobotanical values. The identification results will serve as a reference for the development of science learning resources and support the creation of contextual teaching materials for junior high school students in Burai Village The study applied a descriptive qualitative method with field surveys, observations, and in-depth interviews with traditional leaders and local residents. Data were analyzed through identification of species, uses, and cultural significance. The results identified 16 species of wetland plants utilized for food, traditional medicine, handicrafts, construction materials, and cultural ceremonies. Species such as Hymenachine amplexicaulis, Melaleuca leucadendron, Nelumbo nucifera, Eleocharis dulci, and Nypa fruticans are essential in daily life. The findings indicate that wetland vegetation plays a crucial role in supporting local livelihoods, preserving traditional knowledge, and maintaining cultural identity. This study emphasizes the importance of integrating local wisdom into sustainable wetland management to ensure ecological and cultural preservation in Burai Village